Тransplantation of autologous stem cells, obtained from adipose tissue, in complex treatment of chronic ischemia of the lower extremities - V. G. Mishalov; N. Yu. Litvinova; O. I. Kefeli-Yanovska; V. A. Chernyak; D. E. Dubenko; E. A. Dzhalilova; O. I. Azarov; R. F. Kaminsky (Клінічна хірургія, 2018)
Objective. To investigate the efficacy of application of autologous mesenchymal stem cells (AMSC) in treatment of patients, suffering critical ischemia of the lower extremities (CILE). Маterials and methods. In 2012 - 2015 yrs there was conducted the treatment of 41 patients, suffering CILE: 22 (53.7%) - men, and 19 (46.3%) - women. In the Group I (the main) 21 (51.2%) patients have had obtained a standard course of treatment, using AMSC. In the Group II (the control one) 20 (49.8%) patients have obtained a standard course of conservative treatment, using prostaglandins of group Е1 (PGЕ1). The results were investigated, measuring ankle-brachial pressure index, and the indices of a laser duplex flowmetry and a walking distance.